A New Approach to Quantifying Raw Material Selectivity in the African Acheulean: Perspectives from Angola and South Africa - (:unkn) unknown (My University, 2021)
Abstract In southern Africa, the use of gravel outcrops has been recorded at a range of Earlier Stone Age sites, and this raises questions about the diversity of raw material sourcing practices adopted by hominins. To assess the existence of sourcing strategies, this study details a new morphometric analysis method that investigates the influence of pebble and cobble shape at two Acheulean case-study sites: Dungo IV (Benguela Province, Angola) and Penhill Farm (Eastern Cape Province, South Africa). Since these assemblages present frequent pebble and cobble artefacts, we investigate these to identify raw material blank properties to then establish whether these properties were intentionally selected for. To do so, we analyse each archaeological sample separately via a technological and morphometrical approach and then compare them with geological samples obtained during fieldwork survey. Overall, these two case studies provide some illustration of variable selection strategies within the southern African coastal plain.
Keywords: African Research